The Effect of a "Class Smoke Free Pledge" on Breath Carbon Monoxide in Arabic Male Adolescents. Issue 5 (3rd March 2017) - Al-sheyab, Nihaya A; Khader, Yousef S; Shah, Smita; Roydhouse, Jessica K; Gallagher, Robyn
Abstract: Introduction: Arabic male adolescents have a high smoking prevalence. Introduction of "Class smoke-free" pledges have been successful amongst European adolescents but have not been evaluated using objective valid measures. We tested the impact of adding a smoke free pledge strategy to a proven peer-led asthma and smoking prevention program on breath carbon monoxide level (BCO) in male high-school students in Jordan. Methods: We enrolled male students from four high-schools in Irbid, Jordan. Schools were randomly assigned to receive either TAJ (Triple A in Jordan, n = 218) or TAJ-Plus (with added class smoke-free pledge, n = 215). We hypothesized that students receiving TAJ-Plus would have greater reduction in BCO levels than those only receiving the TAJ intervention. Asthma and smoking status were assessed by self-administered questionnaires. Smoking outcomes were collected using a BCO Monitor. Results: Both groups had significant reductions in BCO levels post-intervention ( p < .0001), however, decreases were greater in TAJ-Plus group (3.9 ± 0.2 vs. 4.8 ± 0.2, p < .0001). Intervention effects on BCO over time did not vary by smoking status ( p = .085), asthma status ( p = .602), or a combination of the two ( p = .702). Conclusions: An added smoke-free pledge strategy to a proven peer-led asthma education program appears to be a promising approach to motivate adolescents to abstain from smoking in Jordan. Future research is required to determine if these results can be extended to Jordanian adolescent females. Implications: A commitment by students via a "class smoke-free" pledge can be an added incentive to motivate adolescents in Arabic-speaking countries to abstain from smoking. Social influence approaches in schools can be useful in countering the aggressive tobacco marketing campaigns targeting Jordanian and other Arabic-speaking youth. The combination of "class smoke-free" pledges and an evidence-based peer-led asthma and smoking education can be implemented in schools to influence adolescents with asthma to abstain from smoking.